Success factors in a reward and equity based crowdfunding campaign - Pereira, L.; Ferreira, F. (2018 IEEE International Conference on Engineering, Technology and Innovation, ICE/ITMC 2018, 2018)
As the world changes, financial sector changes with it, and alternative finance emerge. Crowdfunding is part of this evolution and its use is becoming more widespread day by day. As more entrepreneurs and organizations seek crowdfunding to fund their ventures, and to solve the most important obstacle to achieve a successful crowdfunding campaign, which is not the information available about how to create a successful campaign, but rather its dispersion, it becomes of uttermost importance to create a framework to help them to succeed raising finance. It is, therefore, the main goal of this paper, to provide a valuable guide to help entrepreneurs in the hard task of raising finance through crowdfunding, mainly those using equity and reward crowdfunding. To accomplish the purposed goal, it is important to understand the underlying motivations of those investing in crowdfunding, in order to offer them what they seek and what motivates them. It is also essential to identify which kind of crowdfunding fits better the entrepreneur's goals and which one increases the likelihood of achieving them. Finally, is crucial to understand the specific success factors for a successful crowdfunding campaign. One of the main findings of this work, is that the motivations for investors in equity and reward crowdfunding are similar. This is very important, since it solves the problem of the scarcity of data for the equity model. With similar motivations it is possible to apply the data available for reward crowdfunding to equity crowdfunding, since both campaign can be design to answer the same needs and motivations.